Spiritual And Aesthetic Development Of Sports In Ancient Western Philosophical Thoughts (Zien Journal of Social Sciences and Humanities, 2025)
In the ancient West, especially in Greece, the main attention was paid to the formation of a person's physical development, spiritual and aesthetic appearance. The Greeks considered Apollo the highest symbol of human physical perfection and the god of art and artistic inspiration. For this reason, the demonstration of human perfection was the main idea of the Olympic Games. That is why the Olympic Games, the supreme sports festival of the ancient Greeks, were associated with such artistic competitions as music and Sharia. After sports competitions on the field, real athletes also participated in artistic competitions. Based on this, we can say that the Olympic Games invited philosophers, musicians, poets, sculptors, artists, along with athletes, to the stadium's treadmills, to the fields where competitions were held.